2017
DOI: 10.5620/eht.e2017014
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption, mercury exposure, and the risk of cholesterol profiles: findings from the Korea National Health and Nutrition Examination Survey 2010-2011

Abstract: In this study, the associations between mercury (Hg) exposure and cholesterol profiles were analyzed, and increased Hg levels and cholesterol profiles according to the amount of fish consumption were evaluated. Data on levels of blood Hg, the frequency of fish consumption, total blood cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) in 3951 adults were obtained from the Korea National Health and Nutrition Examination Survey 2010-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…31 Another study showed a positive association between Hg exposure, total cholesterol, and LDL-C levels. 32 As expected, our study is not without limitations. Like any other cross-sectional study, it focused more on prevalence rather than incidence.…”
Section: Factorsupporting
confidence: 56%
See 1 more Smart Citation
“…31 Another study showed a positive association between Hg exposure, total cholesterol, and LDL-C levels. 32 As expected, our study is not without limitations. Like any other cross-sectional study, it focused more on prevalence rather than incidence.…”
Section: Factorsupporting
confidence: 56%
“…31 Another study showed a positive association between Hg exposure, total cholesterol, and LDL-C levels. 32…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kristal-Boneh et al showed that the subjects exposed to lead had higher serum total cholesterol levels compared to those that did not 33 . Cho et al also found a strong link between mercury exposure, LDL-C levels, and total cholesterol in the Korean general population 34 . In vivo studies also showed that an increase in serum cadmium levels was associated with increased levels of serum total cholesterol, LDL-C and triglyceride, and reduced HDL-C and glutathione levels 35 , 36 .…”
Section: Discussionmentioning
confidence: 91%
“…Hypertriglyceridemia is defined as abnormal TG levels in the blood and is associated with other lipid and metabolic derangements [ 43 ]. Hypertriglyceridemia is defined as fasting TG levels ≥200 mg/dL according to the recommendation of the NCEP and previous studies [ 24 , 44 , 45 ]. Therefore, in this study, hypertriglyceridemia was defined as fasting TG levels ≥200 mg/dL.…”
Section: Methodsmentioning
confidence: 99%